2002
DOI: 10.1046/j.1463-1318.2002.00359.x
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of hydrogen peroxide‐enhanced ultrasound in the identification of internal openings of anal fistulas

Abstract: OBJECTIVE: This prospective study was designed to assess the accuracy of hydrogen peroxide-enhanced ultrasound in the identification of internal openings of anal fistulas, with surgical findings as the golden standard. PATIENTS AND METHODS: A total of 143 consecutive patients (102 men; mean age, 45 years) with fistula-in-ano were assessed by hydrogen peroxide-enhanced ultrasound before surgery involving one radiologist. Ultrasound was performed using a B & K Diagnostic Ultrasound System trade mark with a 10-MH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 8 publications
0
7
1
1
Order By: Relevance
“…However, it seems that the accuracy of endosonography depends to a large extent on the criteria used to identify the internal opening rather than on the technique of endoanal ultrasound. In studies in which the three criteria were used, the accuracy of H 2 O 2 -enhanced ultrasound for detecting the internal opening was 68 percent, 3 which is higher than the 62 percent reported in our study using two criteria, 4 and much higher than 48 percent reported by Poen et al, 5 who used only criterion III.…”
contrasting
confidence: 69%
“…However, it seems that the accuracy of endosonography depends to a large extent on the criteria used to identify the internal opening rather than on the technique of endoanal ultrasound. In studies in which the three criteria were used, the accuracy of H 2 O 2 -enhanced ultrasound for detecting the internal opening was 68 percent, 3 which is higher than the 62 percent reported in our study using two criteria, 4 and much higher than 48 percent reported by Poen et al, 5 who used only criterion III.…”
contrasting
confidence: 69%
“…Patients were selected before operation based on digital examination, proctosigmoidoscopy and hydrogen peroxide-enhanced ultrasonography 13 . Those with a history of fistula surgery also underwent magnetic resonance imaging studies.…”
Section: Methodsmentioning
confidence: 99%
“…In this respect, endoanal ultrasonography (EAUS) has become a mainstay in the preoperative assessment of complex fistulae-in-ano [5], showing a high sensitivity and positive predictive value for comparison of fistula anatomy with surgery [6,7]. Cheong and colleagues were the first to describe hydrogen peroxide-enhanced EAUS in anorectal sepsis [8], where its addition has been shown to have a higher sensitivity for the detection of the internal fistula opening in both cryptogenic never operated [9] and recurrent [10] fistulae-in-ano.…”
Section: Introductionmentioning
confidence: 99%